Transformacja funkcjonalna zachodniej części regionu łódzkiego. Rozwój pasma turystycznouzdrowiskowego: stan i perspektywy - Cieślak, Adriana, B. (Lodz University of Technology Press, 2016)
Healing thermal waters are becoming an important development factor of the Łódź region. The precursor of activities aimed at development of a health resort function is Uniejów, the town, which in no time has become a thermal spa widely recognized in the country. The creation of the spa in Uniejów has also initiated an intensive development of health tourism in a regional scale. Intensive activities cover especially the western part of the region, which is reflected in the formation of a tourist-spa zone as well as the implementation of the Central Tourist Arc project. The article focuses on issues related to the dynamics of the functional and spatial changes in Uniejów and its surroundings. The essence of the research is a preliminary evaluation of transformations with special focus on the cultural landscape of the town. In a regional scale, the direction and nature of the transition associated with the activation of the health resort function were analyzed and evaluated. The essence of the study is to assess the potential and the risks of the changes. The effect of the works is an attempt to create general demands in terms of space and cultural resources management, in case of the development of a new health resort product.
Functional transformation of the western part of the Łódź region. The development of tourism and spa zone: current status and prospects
Keywords: revitalization urbanized areas; revitalization process; rewitalizacja obszarów zurbanizowanych; proces rewitalizacji